Titer Differences in Rheumatoid Factor Level in The Elderly Using The Glycine Saline Buffer Reagent and 0.9% NaCl Ready to Use - Bastian Darwin (IKesT Muhammadiyah Palembang, 2023)
Introduction: The incidence of Rheumatoid Arthritis (RA) in Indonesia has a case prevalence ranging from 0.1% to 0.3%. Limitations in the supply of Glyceline saline buffer in laboratory examinations, especially in the laboratory for examination of Rheumatoid Factor (RF), is one of the reasons for the need for alternative materials with the same effectiveness to be used in examinations. An alternative in carrying out inspections if commercial reagents are not available so that ready-to-use 0.9% NaCl reagent can be an alternative reagent. The purpose of this study was to determine whether there were differences in the titers of rheumatoid factor levels using glycine saline buffer reagents and ready-touse 0.9% NaCl. Method: The study was conducted at the IKesT MP Clinical Pathology Laboratory. The research design used a posttest only control group design. The population is 43 elderly people at the Harapan Kita Nursing Home. a sample of 30 elderly people with purposive sampling technique. Data were analyzed by Wilcoxon test. Results: The results obtained were p = 0.000 for titer examination of RF levels using Glycine Saline Buffer reagent and ready-to-use 0.9% NaCl reagent. Discussion: There are differences in the titers of rheumatoid factor levels using glycerin saline buffer and ready-to-use NaCl. 0,9%.